Fieldwork: Utilizing the Environment for Comprehensive Geography Learning - Daska Azis; M Hafizul Furqan; Suhendro; Muhammad Al-Farisy; Ahmad Nubli Gadeng; Mirza Desfandi; Rizka Dewantara; Cut Meurah Badriatun Nufus; Rahmilia Hadiyani (JURNAL GEOGRAFI, 2025)
This study provides an overview of how the Field Trip learning method can be used in school geography by utilizing natural and artificial laboratories. Geography education includes various components, including the lithosphere, anthroposphere, hydrosphere, biosphere, and atmosphere. One effective method to enhance learning is to utilize the environment as a resource through fieldwork, where students engage in direct observation and investigation outside the classroom. The research method uses a qualitative approach with literature studies and bibliographic analysis. The findings show that natural and artificial environments can support fieldwork-based learning, including (1) studying the distribution of flora and fauna in urban forests, (2) understanding natural disasters through visits to the Tsunami Museum, (3) applying remote sensing techniques by exploring hilly landscapes, and (4) utilizing university laboratories for Geographic Information Systems. The fieldwork method encourages interactive learning between teachers and students and peer involvement, creating a fun yet focused learning experience. In addition, incorporating the environment as a learning resource enhances students' critical thinking, encourages active participation, and fosters a scientific mindset. Students gain deeper geographical insights through this approach while developing important analytical and observation skill